Screen Printed Based Impedimetric Immunosensor for Rapid Detection of Escherichia coli in Drinking Water - Cimafonte, Martina (Sensors (Basel), 2020)
The development of a simple and low cost electrochemical impedance immunosensor based on screen printed gold electrode for rapid detection of Escherichia coli in water is reported. The immunosensor is fabricated by immobilizing anti-E. coli antibodies onto a gold surface in a covalent way by the photochemical immobilization technique, a simple procedure able to bind antibodies upright onto gold surfaces. Impedance spectra are recorded in 0.01 M phosphate buffer solution (PBS) containing 10 mM Fe(CN)(6)(3−)/Fe(CN)(6)(4−) as redox probe. The Nyquist plots can be modelled with a modified Randles circuit, identifying the charge transfer resistance R(ct) as the relevant parameter after the immobilization of antibodies, the blocking with BSA and the binding of E. coli. The introduction of a standard amplification procedure leads to a significant enhancement of the impedance increase, which allows one to measure E. coli in drinking water with a limit of detection of 3 × 10(1) CFU mL(−1) while preserving the rapidity of the method that requires only 1 h to provide a “yes/no” response. Additionally, by applying the Langmuir adsorption model, we are able to describe the change of R(ct) in terms of the “effective” electrode, which is modified by the detection of the analyte whose microscopic conducting properties can be quantified.